Case report: Application of metagenomic next-generation sequencing in the diagnosis of visceral leishmaniasis and its treatment evaluation - Liang, Qiuping; Liang, Xiaogong; Hong, Dengwei; Fang, Yuan; Tang, Lanlan; Mu, Jiao; Tan, Xiaoli; Chen, Feng (Frontiers in Medicine, 2023)
Visceral leishmaniasis is a vector-borne infection by the Leishmania spp., a parasite. Although the overall incidence of visceral leishmaniasis is low, the disease still occurs frequently in some high-risk areas. In our study, two patients were admitted to the hospital with an unprovoked and recurrent high fever, and the condition was not improved after antibiotics administration. Meanwhile, bone marrow aspiration smears failed to find out any pathogen. Finally, Leishmania-specific nucleic acid sequences were successfully detected in the peripheral blood of two patients through metagenomic next-generation sequencing (mNGS), which was further confirmed by bone marrow smear microscopy and antibody tests. After targeted treatment for visceral leishmaniasis in the patients, mNGS reported a decrease in the reads number of Leishmania sequence. The results indicate the feasibility of mNGS in detecting Leishmania spp. in peripheral blood samples. Its therapeutic effect evaluation may be achieved through a comparative analysis of the number of reads before and after the treatment.